2012
DOI: 10.1080/07448481.2012.690465
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Asymptomatic Nonurethral Gonorrhea and Chlamydia in a Population of University Men Who Have Sex With Men

Abstract: The incidence of pharyngeal gonorrhea and rectal chlamydia in MSM who visited the Columbia Health Service was similar to rates of asymptomatic nonurethral gonorrhea and chlamydia in studies conducted in the MSM population in non-university settings. This suggests that, following the Centers for Disease Control and Prevention guidelines, 3-site testing for MSM seen at the Columbia clinic is indicated. NAAT is more sensitive than culture for nonurethral gonorrhea and chlamydia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…18,19 The rates of rectal chlamydial infection in men who have sex with men (MSM) have been reported to be between 3% and 10.5% in some settings. 20,21 An 8.4% prevalence of anorectal C. trachomatis in women has been reported and almost all (94.5%) of these women also had urogenital C. trachomatis . 22,23 Pharyngeal chlamydial infections are also usually asymptomatic, but symptoms of a mild sore throat can occur.…”
Section: Clinical Features Complications and Sequelaementioning
confidence: 99%
“…18,19 The rates of rectal chlamydial infection in men who have sex with men (MSM) have been reported to be between 3% and 10.5% in some settings. 20,21 An 8.4% prevalence of anorectal C. trachomatis in women has been reported and almost all (94.5%) of these women also had urogenital C. trachomatis . 22,23 Pharyngeal chlamydial infections are also usually asymptomatic, but symptoms of a mild sore throat can occur.…”
Section: Clinical Features Complications and Sequelaementioning
confidence: 99%
“…21,22 However, several obstacles impede implementation of these recommendations, including perceived or actual cost of testing, lack of test kit availability, and insufficient awareness of the need to screen asymptomatic individuals at all relevant anatomic sites. 21,23 These difficulties are likely to be of greater impact in settings such as Thailand, where HIV prevalence and incidence among MSM are high and where lack of epidemiological data and cost of testing may impede routine screening. 24,25 For example, in Chiang Mai, Thailand, during the course of STI screening for the Pre-Exposure Prophylaxis Initiative trial, only 4 cases of CT and NG infection were confirmed in 22 individuals, with STI symptoms consenting to evaluation, among 551 study volunteers.…”
mentioning
confidence: 99%
“…The laboratory system used unique test numbers to distinguish rectal, pharyngeal, and urethral or urine specimens. Because nucleic acid amplification tests (NAATs) have not been cleared by FDA for the detection of rectal and oropharyngeal GC and CT infection, the laboratory had previously validated testing of rectal and pharyngeal specimens with NAATs to report results for patient management [11,12]. In this analysis, tests on urogenital specimens ordered under this test code will be referred to as urine.…”
Section: Methodsmentioning
confidence: 99%